Geospatial science for smart land management an Asian context - Vries, Walter Timo de; Rudiarto, Iwan; Piyasena, N. M. P. Milinda (Boca Raton, FL CRC Press, 2024)
Responsible land distribution in Asia, with ever-increasing limitations in space, requires the use of smart technologies, sophisticated models, intelligent algorithms, and big data repositories. This book presents new land management perspectives and fit-for-purpose, flexible, dynamic, and effective solutions for land management and land administration problems. Case studies written by global experts from different Asian countries, including China, India, Indonesia, Iran, Japan, and more, demonstrate how and why the uptake of geospatial technologies is booming, and how to handle land scarcity and competing spatial interests in both urban and rural areas in Asia"-- Provided by publisher.
Geospatial science for smart land management in Asia -- Trends in geospatial technologies in Asia -- Advancing geospatial technology to construct fit-for-purpose land administration and land management in ASEAN countries -- The congruence and conflicts of spatial data infrastructure and cadastral agricultural systems in Pakistan -- Digital transformation in Indonesian land administration: further developments and directions -- Urban growth modelling for a city built from scratch - case study of the new Indonesian capital -- Developments of 3D cadastres in the Asian context -- Flood modeling and prediction towards smart land management in Sri Lanka -- Machine learning and meta-heuristic optimization algorithms for land cover classification -- Trends in smart land management and smart spatial planning in Asia: case study of the new capital city of Indonesia -- Evaluate the existing proposals of re-engineering the land administration system in Sri Lanka against the fit-for-purpose approach -- A review of Sri Lanka's National Spatial Data Infrastructure (SL-NSDI) with the aim of enhancing its functionalities -- Digital administration of land data: a case from National Housing and Urban Development Corporation -- Reducing rural boundary conflict through participatory mapping and GNSS-GIS -- An analysis of urban and rural development for the conception of a national spatial plan in Thailand -- Drone technology, rapid titling, and value creation: early insights from India's SVAMITVA scheme -- Geospatial application of open geospatial data analysis for land use-change detection: a case study from Japan -- Assessment of urban patterns using spatial metrics and prediction of urban growth: A case study of Kabul, Afghanistan -- A geospatial analysis for an integrated land use and water strategy for Bagmati River in Kathmandu Valley, Nepal -- Developments geospatial sciences for smart land management in China: theory and practice -- Accuracy assessment of the drone survey parameters for cadastral purposes -- Artificial intelligence (AI) assisted precision agriculture: applications in Asian context -- The dynamics of village land management: a case from central Java, Indonesia -- Toll road construction and its impact on paddy fields, production and the regional development of the Semarang-Surakarta corridor, Indonesia -- Jam tomorrow: towards sustainable coastal urban development in the era of uncertainty -- Ethical and legal issues affecting geospatial sciences and advances in smart land management -- Advancing research in geospatial sciences for land management in Asia.
Includes bibliographical references and index.
Keywords: Geospatial data -- Asia; Land use -- Management. -- Asia; Land use -- Planning. -- Asia